A techno-economic analysis method for guiding research and investment directions for c-Si photovoltaics and its application to Al-BSF, PERC, LDSE and advanced hydrogenation. Issue 5 (2nd March 2018) - Chang, Nathan L.; Ho-Baillie, Anita; Wenham, Stuart; Woodhouse, Michael; Evans, Rhett; Tjahjono, Budi; Qi, Fred; Chong, Chee Mun; Egan, Renate J.
Abstract : Uncertainty analysis combines cost, performance and market factors to guide research and investment decisions for selected c-Si PV technologies. Abstract : A techno-economic analysis method is used to analyse industry standard mono crystalline silicon photovoltaic technologies – Aluminium Back Surface Field (Al-BSF) and Passivated Emitter and Rear Cell (PERC), together with promising process variations – Laser Doped Selective Emitter (LDSE) and three implementations of advanced hydrogenation. Building on a previously reported manufacturing cost and uncertainty analysis method, the impact of uncertainty in module performance and market price is added to estimate the manufacturer's gross margin. Two additional interpretation methods are described – (i) simultaneous Monte Carlo and (ii) contribution to variation – that help distinguish the impact of small differences between sequences, and identify the most important factors (cost, performance or market) affecting commercial viability. Combining these methods allows a rapid commercial viability assessment without requiring exact data on all the inputs. The analysis indicates that PERC is more commercially attractive than Al-BSF, with a median improvement in manufacturer's margin >5%. Al-BSF + LDSE is found to reduce manufacturer's margin. The PERC + LDSE and PERC + advanced hydrogenation sequences are estimated to provide a median margin improvement >2% compared to PERC alone. The advantage of PERC + LDSE depends strongly on delivering the expected 0.9%abs cell efficiency gain with high production yields and receiving a selling price premium for higher power modules; less important is the production cost of the LDSE process steps. The advantage of advanced hydrogenation depends strongly on achieving the expected 0.2%abs as-produced efficiency gain with high production yield, as well as realising a 0.5% selling price premium for being "CID-Free"; these factors outweigh the production costs of the alternative hydrogenation processes.